2011
DOI: 10.4236/health.2011.312119
|View full text |Cite
|
Sign up to set email alerts
|

Does conventional phototherapy have any effect on platelet count in full term neonates with indirect hyperbilirubinemia?

Abstract: Mean platelet count after phototherapy was higher than that before treatment. The study had propounded that mean platelet count increased with extended mean phototherapy time. This study had propounded this hypothesis that phototherapy in full term icteric newborns leads to increased platelet count. It may be due to accelerated platelet turnover in peripheral microvasculature with adequate platelet reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…The mean platelet counts have increased in neonates who received phototherapy for 48-72 hours which is contrary to our study. 9 Thrombocytopenia was seen in maximum number of cases during the first 24 hours of phototherapy, and similar findings were noted in a study. 5,2 That rate of fall of platelet count was more in the first 24 hours of phototherapy which is in contrast to our finding.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean platelet counts have increased in neonates who received phototherapy for 48-72 hours which is contrary to our study. 9 Thrombocytopenia was seen in maximum number of cases during the first 24 hours of phototherapy, and similar findings were noted in a study. 5,2 That rate of fall of platelet count was more in the first 24 hours of phototherapy which is in contrast to our finding.…”
Section: Discussionsupporting
confidence: 85%
“…Platelets which had been briefly exposed to light following photosensitization by hematoporphyrin lost the ability to aggregate and release potassium, acid phosphatase, serotonin and adenosine Shah MH et al Int J Res Med Sci. 2019 Sep;7 (9): [3505][3506][3507][3508][3509] International Journal of Research in Medical Sciences | September 2019 | Vol 7 | Issue 9 Page 3506 triphosphate. Electron photomicrographs of these altered platelets showed depletion of cytoplasmic materials and smooth membrane contours as compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…. DISCUSSION Thrombocytopenia as a side effect following exposure to phototherapy was documented by our study.The overall incidence of thrombocytopenia was 7.5% .this came in agreement with Khera and Gupta, 2011 (5) and Shah et al, 2019 (6) who showed that phototherapy was complicated by thrombocytopenia in 35% and 45.6% of neonates who received phototherapy.In disagreement with our study, the study done by Monsef et al ., 2011 (7) which reported that there was an increase in the platelet count after phototherapy As regarding to severity of thrombocytopenia, our study showed that 3 neonates (33.3%), 4 neonates (44.4%) and 2 neonates (22.2 %) of neonates who developed thrombocytopenia had mild, moderate and severe thrombocytopenia respectively. In disagreement with our study, the study of Khera and Gupta, 2011 (5) showed that majority of neonates had mild thrombocytopenia (74%), moderate and severe thrombocytopenia was seen in 23% and 3% cases respectively.…”
Section: Figure (12)supporting
confidence: 50%
“…Similarly, no evidence was found for light-induced oxidative stress during phototherapy in newborns [63]. A recent study on in full term neonates with indirect hyperbilirubinemia reported a statistically significant increase in platelet count after phototherapy [64]. However, the increase was only 1/9 th of the esd.…”
Section: Direct Light Effects On Plateletsmentioning
confidence: 88%